Hubungan Komunikasi Terapeutik Dengan Tingkat Kecemasan Ibu Hamil Primigravida - Winarsih, Wiwin; Wulandari, Setyo Retno (Madu : Jurnal Kesehatan, 2024)
Anxiety during pregnancy up to the third trimester affects the birth process, child development, premature birth, low birth weight (LBW), prolonged labor, mental and motor disorders of the child, and even maternal death. In providing midwifery care, one of the competencies that midwives must have been the ability to communicate in midwifery services. Communication skills will underlie efforts to solve client problems, making it easier to provide assistance to clients, both medical services and psychological services are provided with a therapeutic communication approach. Objective: to determine the relationship between therapeutic communication and the level of anxiety of primigravida pregnant women at the Banguntapan II Bantul Community Health Center. Method: This type of research is quantitative with descriptive correlation methods. This research uses a cross-sectional approach. The total population in January was 63 respondents. The sampling method uses a purposive sample technique. The number of samples obtained was 40 respondents. The instrument used is a questionnaire. Results: Based on the results of the Kendall Tau correlation test, a correlation coefficient of -0.329 was obtained with a p-value of 0.006, smaller than 0.05 (p<0.05), so the hypothesis in the research was accepted. Conclusion: there is a relationship between therapeutic communication and the level of anxiety of primigravida pregnant women